Natural product-based bioactive agents in combination attenuate neuroinflammation in a tri-culture model - Liu, Yang; Chang, Dennis; Liu, Tianqing; Zhou, Xian (Frontiers in Pharmacology, 2023)
Neuroinflammation is an important pathological event contributing to the onset and progression of neurodegenerative diseases. The hyperactivation of microglia triggers the release of excessive proinflammatory mediators that lead to the leaky blood-brain barrier and impaired neuronal survival. Andrographolide (AN), baicalein (BA) and 6-shogaol (6-SG) possess anti-neuroinflammatory properties through diverse mechanisms of action. The present study aims to investigate the effects of the pair-combinations of these bioactive compounds in attenuating neuroinflammation. A tri-culture model with microglial N11 cells, microvascular endothelial MVEC(B3) cells, and neuroblastoma N2A cells was established in a transwell system. AN, BA and 6-SG used alone (25 µM) or in pair-wised combinations (12.5 µM +12.5 µM) were subjected to the tri-culture system. Upon the stimulation of lipopolysaccharides (LPS) at 1 µg/mL, tumor necrosis factor-alpha (TNF-α) and interleukin 6 (IL-6) levels were determined by ELISA assays. Immunofluorescence staining was applied to investigate the nuclear translocation of nuclear factor kappa B p65 (NF-κB p65) on N11 cells, expressions of protein zonula occludens-1 (ZO-1) on MVEC cells and phosphorylated tau (p-tau) on N2A cells, respectively. The endothelial barrier permeability of MVEC cells was assessed by the Evans blue dye, and the resistance from the endothelial barrier was measured by transepithelial/endothelial electrical resistance (TEER) value. Neuronal survival of N2A cells was determined by Alamar blue and MTT assays. Combinations of AN-SG and BA-SG synergistically lowered the TNF and IL-6 levels in LPS-induced N11 cells. Remarkably, the combined anti-neuroinflammatory effects of AN-SG and BA-SG remained significantly greater compared to their individual components at the same concentration level. The molecular mechanism of the attenuated neuroinflammation was likely to be mediated by downregulation of NF-κB p65 translocation (p<0.0001 vs. LPS stimulation) in N11 cells. In the MVEC cells, both AN-SG and BA-SG restored TEER values, ZO-1 expression and reduced permeability. Furthermore, AN-SG and BA-SG significantly improved neuronal survival and reduced expressions of p-tau on N2A cells. The AN-SG and BA-SG combinations showed greater anti-neuroinflammatory potential than those used alone in mono- and tri-cultured N11 cells, thereby further protecting endothelial tight junction and neuronal survival. Taken together, AN-SG and BA-SG may provide improved anti-neuroinflammatory and neuroprotective activities.